Oy, My Buenos Aires : Jewish Immigrants and the Creation of Argentine National Identity - Nouwen, Mollie Lewis (Book collections on Project MUSE., 2013)
Between 1905 and 1930, more than one hundred thousand Jews left Central and Eastern Europe to settle permanently in Argentina. This book explores how these Yiddish-speaking Ashkenazi immigrants helped to create a new urban strain of the Argentine national identity. Like other immigrants, Jews embraced Buenos Aires and Argentina while keeping ethnic identities - they spoke and produced new literary works in their native Yiddish and continued Jewish cultural traditions brought from Europe, from foodways to holidays. The author examines a variety of sources including Yiddish poems and songs, police records, and advertisements to focus on the intersection and shifting boundaries of ethnic and national identities. -- Provided by publisher.